The use of traditional weather forecasting by agro-pastoralists of different social groups in Bobirwa sub-district, Botswana - Mosime, Bonolo (Department of Environmental and Geographical Science, 2019)
Agro-pastoralists of Bobirwa sub-district depend mainly on rain-fed agriculture as a source of their livelihood. However, this agro-pastoralism is affected by climatic variability. Advanced warning of upcoming weather information is, therefore, important in informing farming decisions. Traditional weather forecasting is often a major planning tool used to inform agro-pastoralists’ decision making and has been handed from one generation to another. For instance, local knowledge indicators are used to determine onset of rainfall and quality of the rainfall expected. However, there are numerous factors that may have affected the effective use of and dependence on traditional weather forecasting over the years. For this reason, it is critical to examine the current state and use of traditional weather forecasting among the agro-pastoralists. This thesis describes the traditional weather forecasting that agro-pastoralists in Bobirwa sub-district Botswana hold and use in planning for agricultural activities to cope with climate variability. It also examines changes that have been observed in the use of traditional weather forecasting over time. By exploring the knowledge used to generate early warning systems and coping strategies to climate variability of agro-pastoralists, we examine underlying vulnerabilities and resilience possibilities. Data was collected through purposively selecting a total of 101 agro-pastoralists who were further stratified by age and gender. The following qualitative techniques were used in data collection: semi-structured interviews (54 interviewees constituting 37 forecasters and 17 non-forecasters), focus group discussions (47 participants consisting of between 4 and 12 participants), and key informant interviews (11 forecasters who use multiple indicators). The snowballing technique was the main sampling strategy. Knowledgeable traditional forecasters in FGD’s were used to identify key informants with whom semi-structured interviews were conducted. All data was analysed using the thematic analysis method. Data was constructed using a cyclical process to generate themes which consisted of the initialisation (capturing participants’ accounts), construction of themes, relating the themes and developing results. From the study, it was found that male and female elderly agro-pastoralists in Bobirwa are more knowledgeable about traditional weather forecasting and use the traditional weather forecasting techniques to inform their decisions, while the less-knowledgeable adults and youth expressed having limited use of traditional weather forecasting in decision making. There were also differences in the use of specific traditional indicators based on the positionality of an individual in the society as well as age and gender. While the participants indicated that traditional weather forecasting is a reliable technique, climate change is believed to have resulted in unpredictable trends in recent years. For example, excessive floods, patchy and reduced rainfall, extensive heat spells with no specific patterns, changes in biological indicators, and thus, present a challenge to these agro-pastoralists. In all, traditional weather forecasting remains a cultural artefact in the community and will always be practised by the agro-pastoralists. However, many elements threaten the existence of the traditional weather forecasting such as the death of custodians of knowledge, the disruptive nature of climate change, youth migration to cities and the ubiquity of modern practices. Further to this, the prevalence of modern practices, for example Christianity, is transforming the use and beliefs of individuals in traditional weather forecasting leading to reduced intergenerational transfers of the traditional weather forecasting. It is prudent to expect that as cultural practices change within societies, cognisant of the fact that culture is dynamic, it is also expected that the use of traditional weather forecasting will change. It should, however, not be construed that the changes in the use of traditional weather and seasonal forecasting are an indication of the unreliability of traditional indicators, but inability of individuals to forecast. In turn, the study recommends the conservation of the traditional weather forecasting and traditionally important biological indicators. This can be promoted through documentation and teaching of traditional weather and seasonal forecasting techniques in conventional educational programmes. Alongside this, integration of traditional and scientific weather forecasting could be used to develop national policies to facilitate effective drought and flood coping strategies that are inclusive and aimed at limiting the traditional weather forecasting knowledge gap among agro-pastoralists of different age and gender groups. Interventions by the government can be redirected to traditional leaders or elders who bear extensive knowledge on traditional weather indicators to create awareness and facilitate knowledge exchange especially in aiding agro-pastoralists to cope with climate variability. Also, for those who are sceptical of traditional weather forecasting, the use of religious gatherings of different denominations can be an option to facilitate awareness raising of coping strategies that can be explored to reduce vulnerability amongst this group of agro-pastoralists by teaching them to adapt to the changing weather using local knowledge.